Developing workplace injury index (WII) as a measure of safety and health performance in the construction industry in Malaysia - Ali, Hassan; Subramaniam, Chandrakantan; Sri Ramalu, Subramaniam; Mohd Shamsudin, Faridahwati; Ibrahim, Hadziroh (2015)
The construction industry has been generally perceived as being an unsafe and dangerous place of work due to frequent occupational injuries (and fatalities). However, to date, there is no systematic effort in determining the degree of safety and health in this industry.Data on occupational safety and health in this industry are available only in the form of frequency counts but on the severity of injuries.As such, a less meaningful representation of occupational safety and health performance cannot be gauged. Hence, we attempted to develop an index, called Workplace Injury Index, toward this end. To do so, we first identified the common injuries in the construction sector, then ranked them by severity, and finally formulated the index.